2015
DOI: 10.1093/ije/dyv145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the X:IT smoking intervention: a school-based cluster randomized trial

Abstract: Students at intervention schools had a lower risk of smoking after a year of intervention in year 7. This multi-component intervention involving educational, parental and context-related intervention components seems to be efficient in lowering or postponing smoking uptake in Danish adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Several smoking prevention programs have been introduced to schools during the last decades, but many of them have not been effective. In Denmark, the X:IT study has been the first smoking preventive program which has shown significant effect on adolescent smoking [ 34 ]. Our study demonstrated that the effect of the intervention is strongly and positively associated with the degree to which the schools implement the program as intended by the program developers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several smoking prevention programs have been introduced to schools during the last decades, but many of them have not been effective. In Denmark, the X:IT study has been the first smoking preventive program which has shown significant effect on adolescent smoking [ 34 ]. Our study demonstrated that the effect of the intervention is strongly and positively associated with the degree to which the schools implement the program as intended by the program developers.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the program was evaluated using a cluster-randomized controlled trial involving schools from all over Denmark. Intention to treat analyses have shown an overall significant effect of the X:IT intervention [ 34 ], but we do not know whether the effect was differential according to implementation fidelity. In order to investigate whether the full potential of the intervention had been reached, it is therefore important to study implementation of the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Intention to treat analyses showed an overall effect of the X:IT study after 1 year of intervention: odds ratio for smoking among pupils in intervention schools compared with control schools was 0.61 (95% CI: 0.45‐0.81) . The implementation of the program was assessed through a quantitative evaluation of implementation fidelity based on adherence, dose, quality of delivery, and participant responsiveness as recommended by Dusenbury et al Measures of implementation fidelity were combined into an overall school‐wise implementation index, and showed that the implementation of the intervention components in the X:IT study varied across components and over time, and that the program was implemented with high fidelity at one fourth of the schools.…”
Section: Methodsmentioning
confidence: 99%
“…use, all of which are amenable to prevention. Self-esteem training, 44 sensitization to the influence of tobacco advertising, rehearsal of refusal skills, 41 watching 10 truth campaign ads, 45 and using commitment contracts to delay smoking 46 are strategies that may increase resilience to tobacco smoking.…”
Section: Figurementioning
confidence: 99%